1984
DOI: 10.3109/02844318409057406
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler Flowmetry Measurements of Superficial Dermal, Deep Dermal and Subdermal Burns

Abstract: The microcirculation in burned patients' skin has been studied on day 3 after the accident with Laser Doppler Flowmetry (LDF). A schedule for interpretation of LDF values has been designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Clinical prediction of burn depth has been found to be only 65% to 75% accurate compared with biopsy [6,15,9,24]. The current clinical trial finds that assessments which include LDLS imaging can accurately define healing potential in over 90% of cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinical prediction of burn depth has been found to be only 65% to 75% accurate compared with biopsy [6,15,9,24]. The current clinical trial finds that assessments which include LDLS imaging can accurately define healing potential in over 90% of cases.…”
Section: Discussionmentioning
confidence: 96%
“…Good skin blood flow is essential for early burn wound healing. Early studies using the laser Doppler monitoring technique showed a strong correlation between skin blood flow and healing time or need for surgery [6][7][8]. The laser Doppler imaging technique for skin blood flow mapping was introduced by Niazi et al [9] and has become more widely used to aid routine burn assessments [5,[10][11][12] and comparison of treatments [13,14] in recent years.…”
Section: Introductionmentioning
confidence: 98%
“…In the original Doppler flowmetry a fiber optic probe in direct contact with the burn wound was used to assess microcirculation 1 mm below the point of probe tissue contact. Initial studies of burns with the laser Doppler technique were performed by Alsbjorn et al [45]. Baseline measurements and measurements following local heating were made, using a contact probe and rules were derived that defined wounds of different depths that were histologically assessed as either superficial dermal, deep dermal or subdermal.…”
Section: Laser Doppler Imagingmentioning
confidence: 99%
“…108 They showed a correlation between the clinical assessment of burn depth and the local blood flow. In their final study, 109 they scanned 15 burn patients on the third postinjury day and compared the measurements from the laser to clinical judgment and wound biopsies. They found that the laser Doppler correlated closely to histology and was superior to clinical judgment.…”
Section: Laser Dopplermentioning
confidence: 99%